2018
DOI: 10.1080/13548506.2018.1476722
|View full text |Cite
|
Sign up to set email alerts
|

Examining the mediational role of psychological flexibility, pain catastrophizing, and visceral sensitivity in the relationship between psychological distress, irritable bowel symptom frequency, and quality of life

Abstract: The aim of the current study was to use Structural Equation Modelling (SEM) to examine whether psychological flexibility (i.e. mindfulness, acceptance, valued-living) mediates the relationship between distress, irritable bowel syndrome (IBS) symptom frequency, and quality of life (QoL). Ninety-two individuals participated in the study (12 male, 80 female, M = 36.24) by completing an online survey including measures of visceral sensitivity, distress, IBS-related QoL, mindfulness, bowel symptoms, pain catastroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 69 publications
0
11
1
Order By: Relevance
“…The links between EA and psychological well-being have been studied in both medical and non-medical adult populations. High EA is associated with lower quality of life and higher levels of depression, anxiety, stress, and negative affect in both non-medical (Gloster et al, 2017;Hayes et al, 2006;Kashdan et al, 2006) and medical samples such as chronic pain patients (McCracken & Vowles, 2014), irritable bowel syndrome patients (Cassar et al, 2018), cancer patients (Chambers et al, 2016;Gillanders et al, 2015;González-Fernández et al, 2017), and patients with muscle disorders (Graham et al, 2016;Pakenham & Fleming, 2011). Although there has been an increase in the number of publications that describe the links between EA and psychological well-being in medical populations, there continues to be a dearth of research evaluating these links among cardiac patients.…”
Section: Bs_bs_bannermentioning
confidence: 99%
“…The links between EA and psychological well-being have been studied in both medical and non-medical adult populations. High EA is associated with lower quality of life and higher levels of depression, anxiety, stress, and negative affect in both non-medical (Gloster et al, 2017;Hayes et al, 2006;Kashdan et al, 2006) and medical samples such as chronic pain patients (McCracken & Vowles, 2014), irritable bowel syndrome patients (Cassar et al, 2018), cancer patients (Chambers et al, 2016;Gillanders et al, 2015;González-Fernández et al, 2017), and patients with muscle disorders (Graham et al, 2016;Pakenham & Fleming, 2011). Although there has been an increase in the number of publications that describe the links between EA and psychological well-being in medical populations, there continues to be a dearth of research evaluating these links among cardiac patients.…”
Section: Bs_bs_bannermentioning
confidence: 99%
“…[89][90][91] Psychological distress, here defined as the presence of anxiety or depression, is common in IBS. 22,40,41,68 Patients with concurrent anxiety and depression, have more severe symptoms from the GI tract, [92][93][94][95] and visceral hypersensitivity is common. 37,[96][97][98] Psychological distress in IBS is associated with the severity of somatic symptoms, 69,99 lower quality of life, 95,100 and alterations in ANS function, 101 colonic motility, 102,103 and immune function, 104,105 as well as changes in the composition of gut flora.…”
Section: Psychological Factorsmentioning
confidence: 99%
“…34,38,51 It is defined by a decreased pain threshold for visceral distensions or enhanced intensity of visceral sensations. 117 Visceral hypersensitivity has shown associations with the severity of GI symptoms, 37,93 somatization, 118 younger age, 98,118 and, in some studies, with IBS subtype, 51 but diverging associations have been found with psychological distress. 96,118 IBS patients with visceral hypersensitivity have been distinguished from normosensitive patients by reporting more severe abdominal pain and bloating.…”
Section: Visceral Hypersensitivitymentioning
confidence: 99%
“…Taking the abovementioned findings into consideration, it can be said that individuals, who do not show alexithymic features, are psychologically more flexible; therefore, their life satisfaction increases. Individuals, who are aware of their emotions and can express them, are more flexible (Cassar, Knowles, Youssef, Moulding, Uiterwijk, Waters & Austin, 2018), and flexible individuals have higher life satisfaction (Graham, Gouick, Ferreira & Gillanders 2016;Harris, 2016, Kemerli & Çelik, 2015Seyrek & Ersanlı, 2017). The results of Wersebe, Lieb, Meyer, Hofer & Gloster (2018) also support the results of the research.…”
Section: Discussion and Interpretation Of Findings Related To The Relationships Of Alexithymia Psychological Flexibility And Life Satisfamentioning
confidence: 99%